8 - Narrative Dynamics of the Iteso Performers of Ateso Oral Narratives - Ongodia, Simon Peter (Africa Development, 2021)
This article investigates the charged reactions and the narrative dynamics of Iteso Performers in oral narrations in selected Ateso speaking districts of Uganda and Kenya. The article discusses the social functions of oral narratives in the Ateso communities and challenges the view that reciprocal utterances and/or silence from the audience are collaborative. Using quantitative analysis techniques, the study observed that performances often evoked reactions. The article makes a case for performer-audience interaction as co-narrators in a performance and concludes with a strong argument that Ateso narratives can be used to address the numerous socio-cultural and political issues affecting the Iteso. The performers, the study recommends, should consider their audiences as empathically complementary to the narration. Secondly, the efforts of the rather few narrators should be appreciated. Thirdly, the Ministry of Education and Sports in Uganda, should encourage the studying of local languages at all levels.